Kenya : Poverty Reduction Strategy Paper-Joint Staff Advisory Note. (IMF Staff Country Reports; Country Report ;, 2014)
This Joint Staff Advisory Note focuses on the Poverty Reduction Strategy Paper (PRSP) for Kenya. Kenya's second Medium Term Plan (MTP-2) that covers 2013-2017 seeks to build on the successes of the MTP1. It aims to accelerate growth to reach double-digit levels, to create jobs for the Kenyan youth, and to further reduce the still high poverty levels. It highlights that to reduce maternal mortality, the MTP-2 outlines measures such as free maternal healthcare at the point of delivery and incentives for school enrolment.